Civil Code of 1852: The National and the Imported - Luna Victoria León, César (1988)
The text emphasizes that Peru's Civil Code of 1852 marked a milestone in national legislation by attempting to balance imported liberal ideas with the needs of the national context. In this sense, its formation in a period of post-independence political and economic transition, dominated by instability and external influence, is discussed. Likewise, it is commented that, after being in force for 84 years, its effort to modernize the legal order inherited from the colony is appreciated. Nevertheless, the author argues that there are tensions between conservative and progressive approaches to issues such as the ownership of indigenous lands, marriage and slavery. On the other hand, he explains that the Code adopted principles of European liberalism, such as formal equality before the law, but in practice reinforced inequalities by ignoring Peruvian social and economic particularities. Although it represented a significant advance at the time, it was eventually replaced by regulations that were more in line with emerging national needs.